Information systems in forestry - Dykstra, D.P. (1997)
Information has always been an important "stock in trade" of forest managers. Knowledge of tree species, stand age, growth characteristics, site quality, soil and terrain classes, logging costs and products markets have all been essential for profitable forest management for many decades. What has changed is the technology for collecting, analysing and presenting this information, and particularly the speed at which this is done. Forest managers must understand the implications of information and new information technologies and how information needs will affect both the personnel and structure of their organisations. This article considers some emerging information technologies that are becoming important for many forestry organisations as tools to improve strategic and tactical planning and operations management and control.